Da Liga Patriótica do Norte ao 31 de Janeiro : um momento de viragem na história política portuguesa - Pereira, Gaspar Martins (2000)
From the national outrage against the English ultimatum of January 1890 to the Republican uprising of Oporto, we will seek to understand this political turning point, which consisted in identifying the Republican ideal with the nationalist «regenerative» discourse, thus legitimating the revolutionary action. The political manoeuvres of 1890, which initially gave priority of the national issue above the issue of the regime, would come to allow, especially from August when confronted with the collapse of rotativism, the appropriation of that discourse by Republican propaganda.